THE ISSUE OF UNCLAIMED PROPERTY IN STATE OF SELANGOR - Muhammad Azwan Sulaiman; Hadirah Afiqah Hamidon; Nor Nadirah Akmar Mokhtar; Nurul Nadiah Zainol; Mohamad Isa Abdullah (Journal of Islamic, Social, Economics and Development, 2022)
In this research, the issue of unclaimed property in Selangor is being discussed. Unclaimed property has been identified as a significant issue by Malaysian researchers. Wealth cannot be utilized, which is detrimental to the Malaysian economy. It continues to grow year after year, with no end in sight. This research aims to uncover the causes that contribute to estate distribution delay, determine the implications, and identify the legislation issue on these ongoing problems. Unclaimed property is on the rise due to a few circumstances, including lack of public awareness, social and economic concerns, and administrative and legal issues. People educated about property administration will be less likely to inherit a frozen inheritance. The researchers adopted a qualitative technique, asking a series of open-ended questions during a semi-structured interview between December 2021 and January 2022. As the respondents have a general understanding of Islamic estate management and inheritance, a modest sample size is sufficient, and the researchers used judgmental sampling. To identify the code and themes, the researchers employed thematic analysis. As a result, this research provides an overview of the issues and solutions to lowering the rise in unclaimed property.